Studi Fenomenologis Live Streaming Game Mobile Legends Oleh Ustadz Abi Azkakia - Muhammad Revan; Pipir Romadi (Hikmah, 2025)
This article discusses the phenomenon of da'wah through live streaming of Mobile Legends games by Ustadz Abi Azkakia as a response to technological developments and changes in the behavior of the younger generation in accessing religious information. Da'wah, as an obligation of every Muslim, is now transforming from conventional to digital methods by utilizing platforms that are close to young audiences. This study aims to analyze the impact of Ustadz Abi's da'wah on the understanding and religious behavior of mad'u, as well as evaluate the effectiveness of this method compared to conventional da'wah. Using a qualitative and phenomenological approach, the research involved in depth interviews with five informants who regularly watch his live streaming. The results show that this casual approach is able to attract the attention of the younger generation, although there are challenges in ensuring depth of understanding. While not all informants experienced consistent behavioral changes, many felt a strengthening of religious values. Da'wah through digital games has proven to be innovative, but it still needs the integration of conventional methods for maximum results.